Inverse correlation between Helicobacter pylori infection and inflammatory bowel disease. Issue 1 (January 1996) - Halme, L; Rautelin, H; Leidenius, M; Kosunen, T U
Abstract : AIMS: To determine the seroprevalence of Helicobacter pylori in patients with Crohn's disease or ulcerative colitis and in controls without inflammatory bowel disease (IBD). METHODS: One hundred consecutive patients with Crohn's disease, 100 consecutive patients with ulcerative colitis, and 100 age and sex matched controls were studied. Serum H pylori IgG and IgA antibody titres were measured by enzyme immunoassay. RESULTS: The seroprevalence of H pylori was 15% in patients with IBD (13% in patients with Crohn's disease and 18% in patients with ulcerative colitis), whereas the corresponding figure for the controls was 43%. When compared with controls, the seroprevalence of H pylori in patients with IBD was considerably lower in all age groups tested. There was no important difference in treatment with sulphasalazine or in any other medical therapy administered to H pylori positive and negative patients. At the time of blood sampling there was no difference in the level of education or in the employment status between the patients and the controls. CONCLUSIONS: Patients with IBD were less likely to be infected with H pylori than their age and sex matched controls. Neither medical treatment nor socioeconomic factors could explain the difference.